Intensive lifestyle modification program on weight loss and metabolic syndrome risk reduction among obese women in rural areas of Thailand - Charunee Thiabpho; Supranee Changbumrung; Ngamphol Soonthornworasiri; Bencha Yoddumnern-Attig; Patcharaporn Thaboot; Pattharawan Nissayan; Karunee Kwanbunjan (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - The purpose of this paper is to examine the effect of the intensive lifestyle modification program on weight and metabolic syndrome risk reduction in rural obese women who have no underlying non-communicable diseases in Thailand. Design/methodology/approach - A randomized controlled trial was conducted. In total, 60 healthy obese women aged 30-50 years were recruited and randomly assigned to either the intervention (n=30) or control (n=30) group after health screening. Tailored nutritional counseling, health education and exercise training were included in the lifestyle modification program. Behavioral modification techniques were also incorporated. The intervention was conducted weekly for the first eight weeks, then biweekly until week 16. Findings - The student's t-test was used to compare mean difference between groups. The total weight loss in the intervention group (n=29) was significantly higher, 7.6±2.9 kg, compared with the control group (n=30) who lost 0.7±1.4 kg (p<0.001). The intervention group lost weight 10.2 percent from baseline which was significantly higher than that in the control group (p<0.001). Systolic and diastolic blood pressures, fasting blood sugar, and waist circumference were significantly improved. Triglyceride levels slightly improved while high density lipoprotein cholesterol was slightly lowered. The intervention group showed a statistical reduction in abnormal components of metabolic syndrome compared with the control group, with the relative risk=0.24, 95% confidence interval=0.072-0.791, and p=0.018. Originality/value - Compatibility of the program activities conducted by a health professional who had achieved healthy weight loss and accepted as a role model was a key to achieving effective weight loss and metabolic syndrome risk reduction in obese women in rural areas. The program should be integrated into the conventional practice of health care centers.